Development of Seabass (Lates Calcarifer) Nugget Product with Chicken Liver and Egg White Substitution as a Snack for Toddlers - Alfiani, Adinda; Ruhana, Amalia (Jurnal Gizi dan Kesehatan Nusantara, 2025)
Toddlers need more protein and iron than adults and adolescents, namely for protein needs of 2.5 - 3 g / kg BW and iron needs of 7 mg / kg BW. Fish nuggets are one type of snack that is rarely found on the market, so innovation is needed in making fish nugget products. The utilization of snapper fish as a basic ingredient for making fish nuggets is one idea to innovate in making nuggets. This study aims to determine the results of product development, protein and iron content, and the results of the analysis of nutritional content against the RDA in snapper nuggets (Lates Calcalifer) products with chicken liver and egg white substitutions for toddlers. This research is an experimental research that uses RAL research design with 4 treatments, namely factor H as chicken liver substitution with 3 proportions of 10%, 20% and 30% and factor P as egg white substitution with 3 proportions of 5%, 10% and 15%. The analysis of nutritional content tested at the Jember State Polytechnic includes a protein content test using the kjeldahl test which obtained a value of 13.69% for H0P0, 13.94% for H1P1, 14.16% for H2P2, and 14.35% for H3P3. Iron using the Spectrophotometer test obtained a value of 0.47 mg for H0P0, 1.21 mg for H1P1, 1.93 mg for H2P2, and 2.67 mg for H3P3. The fulfillment of protein needs against the Nutritional Adequacy Rate at the age of 6-11 months was 22.6% at H0P0, 26.8% at H1P1, 28.01% at H2P2, and 28.4% at H3P3 and at the age of 1-3 years was 17% at H0P0, 20% at H1P1, 21% at H2P2, and 21.7% at H3P3. The fulfillment of iron requirements against the Nutrient Adequacy Rate at 6-11 months of age was 1.09% at H0P0, 3.27% at H1P1, 5% at H2P2, and 7.09% at H3P3 and at 1-3 years of age was 1.2% at H0P0, 3.6% at H1P1, 5.4% at H2P2, 7.8% at H3P3.